Comparative genomic analysis of bacteriocin genes in Lactobacillus crispatus strains - Giulia Santarelli; Maurizio Sanguinetti; Giovanni Delogu; Flavio De Maio (Scientific Reports)
Abstract Lactobacillus crispatus, a key member of the vaginal microbiota, exhibits strain-specific diversity with important implications for host–microbe interactions and probiotic potential. This study investigates the genomic relationships and bacteriocin diversity across 95 L. crispatus strains to elucidate the mechanisms underlying strain-specific adaptation and microbial competitiveness. Using publicly available data from NCBI, we applied BAGEL4 and core genome multilocus sequence typing (cgMLST) approaches to identify and characterize bacteriocin genes, revealing a high level of conservation of major bacteriocins among strains. Analysis of nucleotide polymorphisms within bacteriocin-encoding sequences showed that these genes are generally conserved, likely due to strong purifying selection. These findings suggest that bacteriocins in L. crispatus are functionally conserved, underscoring their potential role in maintaining vaginal health through microbial competition and pathogen exclusion.